EMPIRICAL STUDY OF THE CHARACTERISTICS OF AFZELIA AFRICANA SEED UNDER COMPRESSIVE LOADING (Nigerian Journal of Technology, 2017)
Afzelia Africana seeds were subjected to quasi-static parallel plate compression test, using Monsanto Tensometer. The loading orientations were horizontal, vertical and edge-to-edge loading positions at four different moisture content levels of 10.6%, 12.8%, 15.2% and 18.4% wet basis (wb). Slight variations were observed in the means of the physical characteristics at varying moisture content in the range of 10.6% to 18.4%. Loading position was shown to have significant effect on all the mechanical properties studied. The rupture force increased with increase in moisture content in horizontal and vertical loading but did not show consistent trend in variation when loaded on the edges. This value was 155.68N for vertical loading, 139.27 N for horizontal loading and 81.0 N for edge-to-edge loading. Hardness ranged from 6.97 to 6.92 N/mm for horizontal loading, 6.92 to 6.67N/mm for edge-loading and 6.99 to 6.93N/mm for vertical loading respectively in the moisture content range of 10.6 to 18.4% for all cases. Rupture energy varied from 104 to 416.33 N-mm on horizontal loading, 59.96to 241.82 on edge-loading and 190.125 to 419.171 Nmm on vertical loading respectively for the same range of moisture content. Toughness varied from 43.758 to 8.865 N-m/mm, 23.563 to 5.370 and 44.667 to 16.349 N-m/mm for horizontal loading, edge-edge orientation, and vertical loading respectively, for moisture content range of 10.6 to 18.4%.Modulusof Elasticity dropped from 35.657 to 28.133 N/mm2 for horizontal loading, from 51.443 to 14.59 for edge-to-edge loading and 38.087 to 41.04 N/mm2for vertical loading in the range of moisture content of 10.6 to 18.4% respectively. The data generated in this study can be applied when estimating the energy and force needed for shelling the seeds and in making useful suggestions on the loading condition that will demand the least energy for the operation and shelling. The physical properties are also useful in process design and analysis.  http://dx.doi.org/10.4314/njt.v36i3.42